Global Health and an Approach to the Problems Undermining Public Health Today: La salud global y una aproximación a los problemas que socavan la salud pública de estos días - Matta Solis, Hernán Hugo (2017)
Global health is defined as a multidisciplinary and interdisciplinary field concerned with improving health and achieving health equity for all people. It transcends national borders, promotes cooperation and collaboration within and beyond the health sciences, and integrates disease prevention with patient care.